Solving engineering-geometrical problems using computer graphics methods - Zhumjumanova, Айнур (Рroblems of engineering and professional education, 2023)
This article talks about different ways to solve engineering geometric problems by means of computer graphics. It talks about what computer graphics is currently very widely used and in what environment it is used